Porous hydroxide nanosheets on preformed nanowires by electrodeposition : branched nanoarrays for electrochemical energy storage - Xia, Xinhui (2013)
Fast, high-yield, and controllable synthesis of functional hydroxide and oxide nanomaterials on conductive substrates is highly desirable for the energy generation and storage applications. For the same purpose, three-dimensional hierarchical porous nanostructures are being regarded advantageous. In this work, we report the fabrication of porous metal hydroxide nanosheets on a preformed nanowires scaffold using the fast and well-controllable electrodeposition method. Co(OH)2 and Mn(OH)2 nanosheets are electrochemically deposited on the Co3O4 core nanowires to form core/shell arrays. Such oxide/hydroxide core/shell nanoarrays can be realized on various conductive substrates. The Co3O4/Co(OH)2 core/shell nanowire arrays are evaluated as a supercapacitor cathode material that exhibits high specific capacitances of 1095 F/g at 1 A/g and 812 F/g at 40 A/g, respectively. The mesoporous homogeneous Co3O4 core/shell nanowire arrays, obtained by annealing the Co3O4/Co(OH)2 sample, are applied as the anode material for lithium ion batteries. A high capacity of 1323 mAh/g at 0.5 C and excellent cycling stability are demonstrated. Our results show that electrodeposition is a versatile technique for fabrication of nanometal oxides on 3-D templates for electrochemical energy applications.